2020
DOI: 10.1002/capr.12320
|View full text |Cite
|
Sign up to set email alerts
|

Developing the competent psychiatric psychotherapist: A single‐site, retrospective study

Abstract: Although a recent survey of applicants to the largest Canadian psychiatry residency programme suggested that emphasis on psychotherapy is a significant motivator for medical school graduates to pursue a psychiatry residency (Wiesenfeld, Abbey, Takahashi, &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These findings suggest that some psychiatry residents may not achieve adequate psychotherapeutic competencies despite national standards for psychotherapy education. Psychotherapy training models are variable in Canadian psychiatry residency programs, despite national training requirements for psychiatry residents [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that some psychiatry residents may not achieve adequate psychotherapeutic competencies despite national standards for psychotherapy education. Psychotherapy training models are variable in Canadian psychiatry residency programs, despite national training requirements for psychiatry residents [14].…”
mentioning
confidence: 99%
“…There may be value in beginning formal psychotherapy training in the first year of residency, given research findings supporting that interest in psychotherapy is highest among first-year psychiatry residents compared with their senior counterparts [16,17]. A recent study demonstrated that early career psychiatrists highly valued the psychotherapy training that they received in the first year of psychiatry residency, even for those psychiatrists who did not subsequently have a psychotherapy-oriented practice [14].…”
mentioning
confidence: 99%